Hyporeactivity of Infection: Potential Limitation to Therapeutic Use of Interferon-Inducing Agents - Stringfellow, D. A. (1972)
Interferon inducers are generally most effective as antiviral agents when used prophylactically. One possible explanation for this is that animals develop a state of hyporeactivity during the course of a virus infection. Such a progressive loss of capacity to produce interferon was observed with a representative group of interferon-inducing agents (polyinosinic-cytidylic acid, Tilorone hydrochloride, New-castle disease virus, or a strain of encephalomyocarditis virus) during the course of a model picornavirus infection in mice.